Evaluation of a school-based reproductive health education program in rural South Western,Nigeria (2007)
This quasi-experimental study compared the relative efficacy of teacher instructions alone, peer education alone, and a combination of these two on reproductive health knowledge, attitude, perceived self-efficacy and sexual practices among secondary schools students in the lbarapa district of Southwestern Nigeria. A baseline questionnaire was administered to a systematic sample of students in four schools that were randomized into four treatment arms: teacher instructions alone (E1), peer education alone (E2), combination of teacher instruction and peer education (E3), and control, The results were used to design the contents of the interventions, which were implemented for one academic session. A follow-up survey using the same sampling procedures as baseline was conducted to measure the outcome of the intervention. The control group had superior reproductive health knowledge at baseline. By follow-up survey however, all three intervention schools showed significant knowledge gains, while the control school students' mean score increased slightly. Increase in knowledge was greatest among E3 (+5.0 points), followed by E2 (+3.4), E1 (+1.4) and C (0.3). The intervention schools showed a significant positive shift in attitude towards use of contraceptives with mean increase of 0.6, 0.5, and 0.9 points in E1, E2 and E3 respectively. Scores that measured the students' perceived self-efficacy for safe sex increased significantly among E1 (from 10.8 to 11.8) and E3 (from 10.4 to 12.6). Reported condom use was significantly higher among E2 (from 16.7 % to 62.8%) (p<0.05) and E3 (from 22.8% to 53%) (p<0.05) compared to E1 (28.6% to 47.4%) (p>0.05) and control (from 25% to 45.8%) (p>O.05). Overall, the students from E3 showed more improvement in knowledge, attitude and self-efficacy, than their counterparts from E2 and E3 and control. Multiple intervention strategies have greater potential of improving reproductive health of students